Thrombotic thrombocytopenic purpura with Graves' disease during pregnancy. Issue 2 (2nd April 2020) - Zhang, Junlin; Baugh, Laura; Guileyardo, Joseph; Roberts, William C.
Abstract: Thrombotic thrombocytopenic purpura may be seen with several autoimmune disorders such as immune thrombocytopenia purpura, immune hemolytic anemia, and systemic lupus erythematosus, but it is rarely associated with Graves' disease. We report a patient with thrombotic thrombocytopenic purpura associated with Graves' disease.